Pseudocapacitance-tuned high-rate and long-term cyclability of NiCo2S4 hexagonal nanosheets prepared by vapor transformation for lithium storage. Issue 19 (18th April 2017) - Song, Yun; Chen, Ziliang; Li, Yanmei; Wang, Qinchao; Fang, Fang; Zhou, Yong-Ning; Hu, Linfeng; Sun, Dalin
Abstract : Well-defined NiCo2 S4 hexagonal nanosheets with a large aspect ratio of ∼45 show pseudocapacitance-tuned high-rate and long-term cyclability for lithium storage. Abstract : The high conductivity of bimetallic thiospinel NiCo2 S4 endows energy storage devices with very fascinating performance. However, the unsatisfactory rate capability and long-term cyclability of this material series significantly limit their large-scale practical applications such as in electric vehicles and hybrid electric vehicles. Herein, we successfully synthesized NiCo2 S4 hexagonal nanosheets with a large lateral dimension of ∼1.35 μm and a thickness of ∼30 nm through a vapor transformation method. The dynamic transformation process of the NiCo2 S4 polycrystalline nanosheets from NiCo-hydroxide has been revealed in detail. Originating from their two-dimensional thin-sheet structure with a high aspect ratio, the induced extrinsic capacitive contribution as high as 91% makes them an ideal candidate for high-capacity and high-rate lithium-ion anodes. The NiCo2 S4 nanosheets deliver a reversible capacity of 607 mA h g −1 upon 800 cycles at a current density of 2 A g −1 . This outstanding long cycle performance sheds light on the structural design of electrode materials for high-rate lithium-ion batteries.